Management of Unilateral Uterine Horn Prolapse in a Full term Pregnant Great Dane Bitch - Devarajan, Reena; Seerangan, Rangasamy; Jayakumar, Umamageswari; Ragunathan, Rajalakshmi; Karuppasamy, Krishnakumar (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
Uterine prolapse, the eversion of the uterine body through the dilated cervix via the vagina, is manifested by a hanging tubular mass out of the vulva. It is an uncommon complication of peripartum or postpartum bitches, usually occurs within 48 hours of whelping and involves one or both uterine horns with distinctly visible prolapsed uterine horn bifurcation outside the vulva (Sathiamoorthy et al., 2013; Battaglia and Steele, 2015). The present communication reports the successful management of peripartum unilateral uterine prolapse in a Great dane bitch by manual reduction and reposition.